Different patterns of neurogenic quadrilateral space syndrome: a case series of undefined posterior shoulder pain - Giuseppe Porcellini; Alberto Brigo; Michele Novi; Elisa De Santis; Silvia Di Giacomo; Andrea Giorgini; Gian Mario Micheloni; Rocco Bonfatti; Alessandro Donà; Luigi Tarallo (Journal of Orthopaedics and Traumatology)
Abstract Background Quadrilateral space syndrome is a painful disorder of the shoulder caused by static or dynamic entrapment of the axillary nerve and the posterior humeral circumflex artery. It was first described in 1983; however, it is an uncommon syndrome that initially presents with nonspecific shoulder pain or selective deltoid atrophy, and diagnosis is often delayed owing to its rarity. Young athletes of overhead sports are more commonly affected by this syndrome. Symptoms of quadrilateral space syndrome include silent deltoid atrophy, persistent posterior shoulder pain, paresthesias, and tenderness over the quadrilateral space. Vascular symptoms may involve thrombosis and embolisms of the upper limb. Instrumental tests and imaging are not always conclusive, leading to frequent misdiagnosis of the syndrome. Patients and methods The aim of this study is to present a case series of four patients diagnosed with neurogenic quadrilateral space syndrome, describe different clinical presentations, and suggest tips for diagnosing this syndrome. All patients underwent a detailed medical history collection, were interviewed about the sports and hobbies they engaged in, and received a comprehensive clinical examination of the neck and shoulder. Patients also underwent diagnostic exams such as magnetic resonance imaging (MRI) and electromyography. An ultrasound-guided injection of local anesthetic was performed into the quadrilateral space. Results All patients affected by neurogenic quadrilateral space syndrome underwent conservative treatment, which included a rehabilitation program. Only one out of four patients experienced complete resolution of symptoms and did not require surgical decompression. Conclusions To properly treat this rare syndrome, we propose classifying it as either “dynamic” or “static,” on the basis of the clinical history, MRI findings, and physical examination. The study includes a rehabilitation program that was effective for one patient, demonstrating that surgical decompression may be avoidable if the cases are promptly diagnosed and classified. Level of evidence IV according to “The Oxford 2011 Levels of Evidence”